Community-driven Development: A Reflection on South Korea’s Saemaul Undong and Its Potential Applications in Indonesia’s Village Funds - Widhiawati, Ni Luh Cindy; Darma, Gede Sri (Journal Public Policy, 2025)
Corruption in village funds is a significant issue in Indonesia, consistently ranking as the highest since 2015. Village funds are intended to enhance government affairs, development, and community empowerment; however, problems such as regulatory misuse and incompetence among village officials persist. This study aims to investigate the impact of Community-driven Development (CDD) on improving people's welfare and enhancing the country's economy, while also analyzing the potential adoption of South Korea's Saemaul Undong program principles in Indonesia's village fund implementation. Employing qualitative methods, primary data were collected via questionnaires from eight beneficiaries across eight different villages, supplemented by secondary data from literature reviews. The findings indicate that CDD empowers grassroots communities to engage actively in their development, with the government playing a vital role in restoring public trust and addressing perceptions of power abuse. Furthermore, integrating Saemaul Undong principles—focusing on infrastructure, land reform, and human resource development—into Indonesia's village fund program can improve rural public service needs. This study fills a literature gap on CDD and village fund management, offering valuable insights for stakeholders and beneficiaries while addressing rising corruption issues.